WALI PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN [LAPAS] NARKOTIKA IIA CIPINANG DITINJAU DARI PERSPEKTIF PEKERJAAN SOSIAL KOREKSIONAL - Ismet Firdaus (Social Welfare Study Program, 2020)
Abstract. The social guardian has a role in rehabilitating the behavior of prisoners or Correctional Assistance Citizens (WBP), in this paper the work of community trustees is viewed from the perspective of Corrective Social Work. The results show that the stages, roles and competencies of correctional caregivers carry out the rehabilitation stages of the therapeutic community model, which is not entirely in accordance with the perspective of corrective work, especially in the aspects of values and skills. Meanwhile, in the aspect of role, the Community Guardian acts as a counselor, broker educator, facilitator and therapist. This roles has not been maximized because the ratio factor beetwen staff and clienis is not ideal. Beside that, in educational competence is inadequate because in the correctional institution there is no have corrective social worker and psychologists are also limited. This implies that social rehabilitation in LAPAS is not maximal. In this research, the Ministry of Law and Human Rights should immediately add correctional guardians with a background in psychologists and corrective social workers who have competencies in accordance with the needs of the Cipinang IIA Narcotics Prison. Abstrak. Wali Wali kemasyarakatan mempunyai peran merehabilitasi perilaku narapidana atau “Warga Binaan Pemasyarakatan (WBP)”, pada tulisan ini pekerjaan Wali kemasyarakatan ditinjau dari perspektif Pekerjaan Sosial Koreksional. Hasilnya menunjukkan bahwa tahapan, peran dan kompetensi wali pemasyarakatan menjalan tahapan rehabilitasi model teraputic community, yang tidak sepenuhnya sesuai dengan perspektik pekerjaan koreksinal, terutama pada aspek nilai dan keterampilan. Sedangkan pada aspek peran, Wali Kemasyarakatan berperan sebagai konselor, educator broker, fasilitator dan terapis. Peran-peran tersebut belum maksimal, karena faktor rasio antara Jumlah Wali Pemasyarakatan dengan jumlah Warga Binaan Sosial tidak ideal. Di samping itu, kompetensi pendidikannya belum memadai karena di lembaga pemasyarakatan tersebut tidak ada seorang pun pekerja sosial koreksional dan Psikolog juga terbatas. Hal ini berimplikasi pada rehabilitasi sosial di LAPAS tersebut menjadi tidak maksimal. Penelitian ini pihak Kementerian Hukum dan HAM harus segera menambah wali pemasyarakatan dengan latar belakang psikolog dan pekerja sosial koreksional yang memiliki kompetensi sesuai dengan kebutuhan LAPAS Narkotika IIA Cipinang.